Zebrafish Establish Female Germ Cell Identity by Advancing Cell Proliferation and Meiosis - Pan, You-Jiun; Tong, Sok-Keng; Hsu, Chen-wei; Weng, Jui-Hsia; Chung, Bon-chu (Frontiers in Cell and Developmental Biology, 2022)
Zebrafish is a popular research model; but its mechanism of sex determination is unclear and the sex of juvenile fish cannot be distinguished. To obtain fish with defined sex, we crossed domesticated zebrafish with the Nadia strain that has a female-dominant W segment. These fish were placed on a ziwi:GFP background to facilitate sorting of fluorescent germ cells for transcriptomic analysis. We analyzed the transcriptomes of germ cells at 10–14 days postfertilization (dpf), when sex dimorphic changes started to appear. Gene ontology showed that genes upregulated in the 10-dpf presumptive females are involved in cell cycles. This correlates with our detection of increased germ cell numbers and proliferation. We also detected upregulation of meiotic genes in the presumptive females at 14 dpf. Disruption of a meiotic gene, sycp3, resulted in sex reversal to infertile males. The germ cells of sycp3 mutants could not reach diplotene and underwent apoptosis. Preventing apoptosis by disrupting tp53 restored female characteristics in sycp3 mutants, demonstrating that adequate germ cells are required for female development. Thus, our transcriptome and gene mutation demonstrate that initial germ cell proliferation followed by meiosis is the hallmark of female differentiation in zebrafish.